Disparities in Hepatitis C Linkage to Care in the Direct Acting Antiviral Era: Findings From a Referral Clinic With an Embedded Nurse Navigator Model - Sherbuk, Jacqueline E.; McManus, Kathleen A.; Kemp Knick, Terry; Canan, Chelsea E.; Flickinger, Tabor; Dillingham, Rebecca (Frontiers in Public Health, 2019)
Background: Direct acting antivirals (DAAs) have simplified and expanded access to Hepatitis C virus (HCV) treatment. Only 17% of the 2.4 million Americans with HCV have linked to HCV care. We aimed to evaluate linkage to care (LTC) in a non-urban HCV referral clinic with a nurse navigator model and identify disparities in LTC. Methods: A single-center retrospective cohort analysis was performed among all patients referred to an infectious diseases HCV clinic between 2014 and 2018. The primary outcome was LTC, defined as attendance at a clinic appointment. A multivariable Poisson regression model estimated the association of variables with LTC. Results: Among 824 referred patients, 624 (76%) successfully linked to care and 369 (45%) successfully achieved sustained virologic response. Forty-six percent of those referred were uninsured. On multivariable analysis, LTC rates were higher among women (Incidence Rate Ratio [IRR] 1.11, 95% CI 1.03–1.20, p-value = 0.01) and people with cirrhosis (IRR 1.20, 95% CI 1.11–1.30, p-value < 0.001). Lower LTC rates were found for young people (<40 years; IRR 0.88, 95% CI 0.79–0.98, p-value = 0.02) and uninsured people (IRR 0.85, 95% CI 0.77–0.94, p-value = 0.002). Among those without LTC, 10% were incarcerated. Race, proximity to care, substance use, and HIV status were not associated with LTC. Conclusions: Using an embedded nurse navigator model, high LTC rates were achieved despite the prevalence of barriers, including a high uninsured rate. Disparities in LTC based on age, sex, and insurance status are present. Substance use was not associated with LTC. Future interventions to improve care should include expanded access to insurance and programs bridging care for incarcerated populations.